An evaluation of an intervention designed to improve the evidence-based supply of non-prescription medicines from community pharmacies. (20th May 2014) - Ngwerume, Karebor; Watson, Margaret; Bond, Christine; Blenkinsopp, Alison
Abstract: Objectives: The aims of this study were to conduct the proof of concept study and to develop and evaluate an educational intervention that promotes the evidence-based supply of non-prescription medicines (NPMs). Method: An educational intervention was delivered to pharmacy assistants and pharmacists in three pharmacies in England. The intervention included the provision of summaries of evidence for the treatment of four minor ailments and resulted in the preparation of evidence-based portfolios for the treatment of the following ailments: athlete's foot, cough, nasal congestion and period pain. The effect of the intervention was evaluated using a combination of direct overt observation, vignettes, self-reported behaviour and interviews. Key findings: Evaluation data were collected from the three pharmacies. Data were derived from 3 pharmacists and 13 assistants, of whom 10 (3 pharmacists; 7 assistants) attended the training event. Comparing pre- and post-intervention practice, 8/11 (pre-) versus 5/6 (post-) observed, 46/80 versus 62/80 vignette and 25/30 versus 39/40 self-reported recommendations were evidence based. Prior to the intervention, 3/16 participants understood the role of evidence regarding the supply of NPMs compared with 16/16 post-intervention. Participants reported relying upon experiential knowledge to inform their decision making prior to the educational intervention. Thereafter, the participants reported using evidence to a greater extent. Barriers and facilitators for evidence-based practice were also identified. Conclusion: A one-off educational intervention increased participants' self-reported awareness and potential application of evidence to inform their supply of NPMs. Further research is needed to assess the effectiveness, long-term impact, generalisability and cost-effectiveness of this intervention for a wider range of common conditions.